2011
DOI: 10.1007/s00228-011-1038-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and current onset delay approaches of type 2 diabetes mellitus (T2DM)

Abstract: The demanding need of treating type 2 diabetes mellitus (T2DM), currently reaching epidemic dimensions, has been the major aim of healthcare systems and policy makers worldwide.Pharmacological treatment associated with lifestyle interventions, in addition to controlling of cardiovascular risk factors, are the main strategies to prevent or delay the onset of T2DM. The present review discusses the state of the art knowledge of effective therapeutic approaches (metformin, thiazolidinediones, nateglinides, α-gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Our study is the first to identify a significant increase in serum PEDF levels in newly diagnosed diabetic patients with no hypertension or dyslipidemia after a 6‐month metformin treatment. Metformin plays an important role not only in the treatment of diabetes but also in its prevention . To the best of our knowledge, there is no previous study concerning the effect of metformin treatment on PEDF levels in diabetes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our study is the first to identify a significant increase in serum PEDF levels in newly diagnosed diabetic patients with no hypertension or dyslipidemia after a 6‐month metformin treatment. Metformin plays an important role not only in the treatment of diabetes but also in its prevention . To the best of our knowledge, there is no previous study concerning the effect of metformin treatment on PEDF levels in diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…Metformin plays an important role not only in the treatment of diabetes but also in its prevention. 19,20 To the best of our knowledge, there is no previous study concerning the effect of metformin treatment on PEDF levels in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is an insulin-resistance condition resulting from various factors. To control diabetes, several medications such as thiazolidinedione and metformin are widely used; these are well-known activators of anti-diabetic signaling molecules (Souto, Souto, Braga, & Medina, 2011). More recently, many investigators have suggested that phytochemicals exert antidiabetic effects by targeting anti-diabetic signaling molecules such as AMP-activated protein kinase (AMPK) and peroxisome proliferator-activated receptor gamma (PPAR-c) (Choi et al, 2011;Guri, Hontecillas, Si, Liu, & Bassaganya-Riera, 2007;Ha do et al, 2009;Hwang, Kwon, & Yoon, 2009;Shehzad, Ha, Subhan, & Lee, 2011;Yin, Zhang, & Ye, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…When activated, AMPK blocks ATP-consuming pathways such as gluconeogenesis, fatty acid synthesis, protein synthesis, and cholesterol synthesis, and triggers ATP generating pathways such as beta-oxidation, glucose uptake, and glycolysis (Ha do et al, 2009;Hwang et al, 2009). Recently, AMPK was shown to be activated by metformin, demonstrating that it is an important target for the development of anti-diabetic medications (Ha do et al, 2009;Hwang et al, 2009;Souto et al, 2011). In addition, several anti-diabetic phytochemicals have also been suggested to target AMPK (Yin et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…It may also exert protective effects on pancreatic islet cells and it is not related to body weight gain. (20) Consideration of metformin use in overweight adolescents not meeting criteria for DM2 is off-label and based on limited published data.…”
Section: Metforminmentioning
confidence: 99%